The Perlocutionary Effect of “Insya Allah” among Indonesians: A Gender-Based Analysis - Sapran, Aditya Rizky Wibisono; Rusmawati, Roosi (Universitas Brawijaya, 2024)
This paper aims to investigate the perlocutionary effects of the utterance Insya Allah in commissive speech acts among Indonesians. Other studies have explored the roles and the illocutionary effects of Insya Allah, but none have pinpointed the perspective of the addressees upon hearing the utterance of a promise. The data were extracted from questionnaire results completed by 20 college students in Malang, an ideal city to represent Indonesia because it has more than 70% of students enlisted from various parts of Indonesia. This paper employs a descriptive qualitative method equipped with various technical analyses. The analysis includes investigations of the perlocutionary effects of Insya Allah. The analysis continues by addressing the details of the perlocutionary effects based on gender, followed by classifying the rationale behind such effects. The findings show a tendency from the respondents of being indecisive as the most prominent perlocutionary effect. The study also reveals three rationales behind the effects: theo-based, trait-based, and experience-based. Despite the religious value of Insya Allah, many Indonesians are reluctant to asso-ciate this utterance when it is inserted into a promise.